Eurobarometer 45.1: European Union rights, sun exposure, work safety, and privacy issues, April-May 1996 - Reif, Karlheinz; Marlier, Eric; Commission of the European Communities (Commission of the European Communities, 2001)
This round of Eurobarometer surveys queried respondents on standard Eurobarometer measures such as public awareness of and attitudes toward the European Union (EU), and also focused on the rights of EU citizens as well as issues of work safety, sun exposure, and personal interviews. Respondents were asked about their knowledge of and the importance of rights such as traveling, working, buying, investing, studying, voting, and receiving medical care anywhere in the EU. Respondents provided further interpretation as to the meaning of some rights by indicating whether the right to live anywhere includes the right to permanently relocate, work, vote, or retire, if the right to work anywhere includes the right to set up a business, receive unemployment, receive retirement pay, or work as a civil servant, if the right to study includes equal access to schools, universities, scholarships, or exchange programs, and if purchasing rights include the right to buy any amount of goods for personal or other use. Questions concerning work safety asked respondents about their satisfaction with steps taken to guarantee health and safety in the workplace and whether employers, government inspectors, worker representatives, company committees, or individual workers should contribute more or less in order to reduce work accidents or work-related illnesses. Responses were also elicited regarding whether health and safety in the workplace contribute to worker efficiency, benefits for the people, economic benefits, and costs that are difficult for the employer to cover. Issues surrounding interviewing and personal data were also investigated. Respondents were asked if interviewing is a proper scientific tool, whether the interview format allows people to express their opinions, and whether it enables decision-makers to take people's views into account. Respondents were also asked if interviewing represents a form of intrusion and whether people need legal protection against the misuse of data. Respondents also indicated whether they thought individuals should have the decision as to whether their personal information can be passed on to someone else. Respondents' attitudes and opinions about sun exposure were also probed. Questions included whether respondents thought sun exposure was good or bad for their health, how best to protect themselves from the sun, and what type of skin, eye color, and hair color they had. Demographic and other background information provided includes respondent's age, sex, marital status, and left-right political self-placement, as well as household income, the number of people residing in the home, and region of residence.

Denna omgång av Eurobarometern undersökte respondenternas inställning till typiska Eurobarometer-mått såsom allmänhetens medvetenhet om, och attityder till, Europeiska Unionen (EU). Därtill sattes fokus på EU-medborgarnas rättigheter, frågor om arbetssäkerhet, solexponering och personliga intervjuer. Respondenterna tillfrågades om deras kunskap om och vikten av sina rättigheter vad gäller resande, arbete, inköp, investeringar, studier, röstning och erhållande av sjukvård inom EU. Respondenterna gav ytterligare tolkningar gällande vissa rättigheter inom olika områden; om rätten att bosätta sig var som helst innebär rätt till permanent bosättning, arbete, röstning och pension, om rätten att arbeta var som helst innebär rätt att starta ett företag, att erhålla arbetslöshetsersättning och pension eller arbeta som statstjänsteman, om rätten att studera innebär lika tillgång till skolor, universitet, stipendier och utbytesprogram, om konsumenträtten innebär rätt att köpa en obegränsad mängd av varor för privat eller annat bruk. Frågor om arbetssäkerhet ställdes gällande deras tillfredsställelse om de åtgärder som vidtagits för att garantera god hälsa och säkerhet på arbetsplatsen och om arbetsgivare, statliga inspektörer, arbetstagarrepresentanter, företagskommittéer eller enskilda arbetare bör bidra mer eller mindre för att minska arbetsplatsolyckor eller arbetsrelaterade sjukdomar. Svar fick också angående huruvida hälsa och säkerhet på arbetsplatsen bidrar till arbetstagarens effektivitet i sitt jobb, fördelar för människor, ekonomiska fördelar, och kostnader som är svåra att täcka för arbetsgivaren. Frågor gällande intervjuer och personliga uppgifter undersöktes också. Respondenterna tillfrågades om intervjuer är en lämplig vetenskaplig metod, huruvida intervjuformatet tillåter människor att uttrycka sina åsikter, och om intervjuer möjliggör för beslutsfattare att ta folkets åsikter i beaktande. Respondenterna tillfrågades också om intervjuer utgör en form av intrång och huruvida människor behöver rättsligt skydd mot missbruk av uppgifter. Åsikter angavs också om de ansåg att individer bör få besluta huruvida deras personliga information kan lämnas vidare till någon annan. Respondenternas attityder till och åsikter om solexponering undersöktes också. Mer specifikt frågades huruvida respondenterna tyckte att solexponering var bra eller dåligt för hälsan, hur de bäst skyddade sig själva från solen samt vilken hudtyp, ögonfärg och hårfärg de hade. Demografisk och annan information samlades in gällande ålder, kön, civilstatus, självplacering på den politiska vänster-högerskalan, hushållsinkomst, antal personer i hushållet och tillhörande region.
Eurobarometer 45.1: European Union rights, sun exposure, work safety, and privacy issues, April-May 1996
EB45.1
Keywords: Social Sciences; Samhällsvetenskap